1980
DOI: 10.1016/0009-2797(80)90050-2
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls as inducers of hepatic microsomal enzymes: Structure-activity rules

Abstract: A number of highly purified polychlorinated biphenyl (PCB) isomers and congeners were synthesized and administered to male Wistar rats at dosage levels of 30 and 150 mumol . kg-1. The effects of this in vivo treatment on the drug-metabolizing enzymes were determined by measuring the microsomal benzo[a]pyrene (B[a]P) hydroxylase, dimethylaminoantipyrine (DMAP) N-demethylase and NADPH-cytochrome c reductase enzyme activities, the cytochrome b5 content and the relative peak intensities and spectral shifts of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…In general, the fewer halogens, the more rapid the metabolic transformation. In other words, PCBs are not only efficacious inducers of xenobiotic metabolism (Parkinson et al, 1980), but may also become substrates for the induced enzymes. Associated with their metabolism may be the metabolic activation to electrophiles and the ensuing reaction with cellular substituents, such as proteins, lipids, and DNA.…”
Section: Metabolic Activation Of Halogenated Biphenylsmentioning
confidence: 99%
“…In general, the fewer halogens, the more rapid the metabolic transformation. In other words, PCBs are not only efficacious inducers of xenobiotic metabolism (Parkinson et al, 1980), but may also become substrates for the induced enzymes. Associated with their metabolism may be the metabolic activation to electrophiles and the ensuing reaction with cellular substituents, such as proteins, lipids, and DNA.…”
Section: Metabolic Activation Of Halogenated Biphenylsmentioning
confidence: 99%
“…The moderately chlorinated isomer groups also contain most of the mixedfunction oxidase (MFO)-inducing congeners. Two of the three pure 3-MC-type inducers and all but two of the mixed-type inducers are penta-, hexa-, or heptachlorobiphenyls (17)(18)(19)(20)(21)(22)(23)(24). The more highly chlorinated congeners are generally less available to organisms both because they are more tightly bound with soils and sediments and because they usually are present in lower quantities in the environment.…”
mentioning
confidence: 99%
“…A study in which wildtype and knockout mouse strains were exposed in utero and by lactation to a complex mixture of PCBs showed that mice with poor-affinity AhR and lacking CYP1A2 (Cyp1a2 (-/-) knockout) had higher concentrations of congeners with no or one ortho chlorine in tissues than mice with high-affinity AhR and CYP1A2 (Cyp1a2 (+/+) wildtype), consistent with low metabolism of these PCB congeners in the knockout mice (Curran et al, 2011). PCBs with two or more ortho chlorines and at least one para chlorine interact with rat and human CAR and induce CYP2B family isoforms, including CYP2B1 and CYP2B6 in a similar manner to the classic inducer, phenobarbital (Parkinson et al, 1980;Al-Salman & Plant, 2012). Some PCBs with two or more ortho chlorines have been shown to bind to the human and rat PXR and to human CAR, resulting in upregulation of CYP3A4 (Waller et al, 1996;Petersen et al, 2007;Al-Salman & Plant 2012).…”
Section: (A) Cypmentioning
confidence: 89%
“…The reason that continuous exposure to certain PCB congeners can affect rate and extent of metabolism is that such exposure can result in upregulation of expression of enzymes that biotransform PCBs, through receptor-mediated processes. PCBs that bind the aryl hydrocarbon receptor (AhR) (see Section 4.3.1) are known to induce CYP isoforms in the 1 family (CYP1A1, CYP1A2 and CYP1B1) as well as epoxide hydrolase, some isoforms of uridine diphosphate-glucuronosyltransferase (UGT) and glutathione S-transferase (GST) (Parkinson et al, 1980;1983). PCBs that bind the nuclears receptors, the pregnane-X receptor (PXR) and the constitutive androstane receptor (CAR) have been shown to induce CYP3A4 and CYP2B isoforms (Petersen et al, 2007;Al-Salman & Plant, 2012).…”
Section: Metabolismmentioning
confidence: 99%